Analisis Penawaran Tenaga Kerja di Provinsi Bali Studi Tahun 2019, 2020, dan 2022 - Hartania, Made Sukma; Cesarie, Herlinda Febrianti (Politeknik Statistika STIS, 2024)
The Corona Virus Disease 2019 (COVID-19) pandemic has an impact on business and labor supply. This research aims to see changes in labor supply in 2019 (before pandemic), 2020 (during pandemic), and 2022 (after pandemic). Year 2021 is not included considering that economic conditions have not fully recovered from the pandemic. The data use is Bali Province’s The National Labour Force Survey (SAKERNAS). The analytical models used in this research are multiple linear regression. Study included the inverse Mills ratio variable to eliminate selective bias which occur as a result of non-random selection of individuals in the model. The results show that there were changes in labor supply in Bali Province. The impact of increasing income during the pandemic on working hours was recorded to be lower when compared to before and after the pandemic. Pandemic shows that the economic shock that occurred affected the labor supply in Bali Province.